2017
DOI: 10.1248/bpb.b16-00694
|View full text |Cite
|
Sign up to set email alerts
|

Xiao Yao San Improves the Anxiety-Like Behaviors of Rats Induced by Chronic Immobilization Stress: The Involvement of the JNK Signaling Pathway in the Hippocampus

Abstract: The current study evaluated the effects of Xiao Yao San (XYS) on anxiety-like behaviors and sought to determine whether the c-Jun N-terminal kinase (JNK) signaling pathway is involved. A total of 40 rats were divided into 5 groups (n 8): the control group (deionized water, per os ( p.o.)), the model group (deionized water, p.o.), the SP600125 group (surgery), the per se group (surgery), and the XYS group (3.9 g/kg/d, p.o.). A 1% dimethyl sulfoxide (DMSO) citrate buffer solution (2 µL/ventricle/d) and SP600125 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
(28 reference statements)
2
8
0
2
Order By: Relevance
“…The two-way regulatory effect of Xiaoyaosan on depression and anxiety has been previously reported. For example, Xiaoyaosan can exert anxiolytic effects through the CRF1 receptor (Jiang et al, 2016) and the JNK signaling pathway (Zhao et al, 2017) and can improve depressive behavior by targeting the Nesfatin-1 receptor (Ma et al, 2019). Our current research confirmed the two-way regulation of anxiety and depression by Xiaoyaosan could be attributed to the alteration in the abundance of intestinal flora and reduction in endotoxin-induced inflammation.…”
Section: Discussionsupporting
confidence: 72%
“…The two-way regulatory effect of Xiaoyaosan on depression and anxiety has been previously reported. For example, Xiaoyaosan can exert anxiolytic effects through the CRF1 receptor (Jiang et al, 2016) and the JNK signaling pathway (Zhao et al, 2017) and can improve depressive behavior by targeting the Nesfatin-1 receptor (Ma et al, 2019). Our current research confirmed the two-way regulation of anxiety and depression by Xiaoyaosan could be attributed to the alteration in the abundance of intestinal flora and reduction in endotoxin-induced inflammation.…”
Section: Discussionsupporting
confidence: 72%
“…The total protein of hypothalamus from each mouse was extracted using RIPA Lysis buffer (Biomiga, Santiago, CA, USA) and the BCA protein assay kit (Termo Fisher Scientific) was used to determine the protein concentration. The protein expressions of apelin and APJ were measured by western blot and the procedure was performed as previously described [ 56 ]. The 12% SDS-PAGE was selected to conduct transmembrane according to relative molecular weight of apelin and APJ, and then proteins were transferred onto polyvinylidene fluoride (PVDF) membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are few reports on the antidepressant effect of XiaoYao pill, the antidepressant effects of XiaoYaoSan and its improved formula Danzhi-XiaoYao-San have been confirmed. XiaoYaoSan improves the anxiety-like behaviors which might be related to the JNK signaling pathway in the hippocampus (Zhao et al, 2017). XiaoYaoSan can exert antidepressant effects by regulating the glutamate/glutamine cycle and the glutamate transporter GLT-1 and the counterpoise kynurenine metabolism pathway (Ding et al, 2017; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%